Comparative in vitro and in vivo pathogenesis of experimentally induced inclusion body disease of boids - Ibrahim, Omar Emad (2013)
The inclusion body disease (IBD) is an infectious fatal disease of boid snakes characterised by behavioral abnormalities, wasting and secondary infections. Microscopically, the disease is identified by the presence of large eosinophilic cytoplasmic inclusions in multiple tissues and thus giving rise to the name of the disease. To date, no exact agent has been conclusively incriminated as the cause of the inclusion body disease (IBD). A total of forty-eight boa and python snakes suspected of (IBD), (15) boa (33) python cases were submitted for necropsy to the Department of Veterinary Pathology and Microbiology, Faculty of Veterinary Medicine, Universiti Putra Malaysia from March 2008 to June 2009 from a recently officiated snake park located 50 kilometres south of UPM. Using a cell culture and in vivo approach to search for the aetiological agent, identification and de novo assembled the cytopathic effects and the morphology and size of two viruses related to small round viruses the size of around 29.5 – 36 nanometer (nm). A continuous Vero cell line was established and used to propagate and isolate the viruses in culture. In total, small round viruses were detected in 20 out of 30 suspected cases of IBD. These viruses have a typical small round viruses organization but were highly divergent. The result of virus clarification showed a visible opaque band, of the purified virus at the 30% interface while the negatively stained particles under electron microscopy showed spherical with icosahedral symmetry viral particles sized between 29.5 – 36.5 nm. More importantly, the two viral isolates, CPE, band, size and morphology were similar for both the boa and python. The presence of small round viruses out of mammals reveals that these viruses infect an unexpectedly broad range of species and represent a new reservoir of potential human pathogens. The findings suggest that IBD is a multisystemic viral infection based on the histopathological findings in the natural cases of IBD in boa and python. In short, it suggests that the incriminating virus or agent is definitely not associated with popularly believed Type-C retrovirus. Twenty five female BALB/c mice (6 – 8 weeks of age) were used to study the pathogenesis apart from verifying Koch’s postulate of IBD via inoculation of boa and python isolates in a murine model. The findings demonstrated the ability of IBD virus from both boa and python to induce an acute and chronic infection in mice. In conclusion, this is the first detailed study on isolated IBD virus in an attempt to adapt the viruses in vitro and assessing their pathogenic potential in a murine model.